2013
DOI: 10.1086/670661
|View full text |Cite
|
Sign up to set email alerts
|

How Individual Movement Response to Habitat Edges Affects Population Persistence and Spatial Spread

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Online enhancements: appendixes. abstract: How individual-level movement decisions in response to habitat edges influence population-level patterns of persistence and spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(143 citation statements)
references
References 58 publications
10
133
0
Order By: Relevance
“…We now study how each of the dispersion relations depend on model parameters. In Figure 5.4, we plot the spreading speed for increasing values of The latter results agree with other authors (Shigesada et al, 1986;Maciel and Lutscher, 2013) as well as with our persistence conditions that show a population will always persist if l 2 is below a threshold value, regardless of the value of ν 2 (plot not shown). The biological explanation of this phenomenon is that an increased value of ν 2 corresponds to a larger probability of individuals to enter bad habitat and therefore decrease the chance of the population to persist.…”
Section: Analysis Of Dispersion Relationsupporting
confidence: 90%
See 3 more Smart Citations
“…We now study how each of the dispersion relations depend on model parameters. In Figure 5.4, we plot the spreading speed for increasing values of The latter results agree with other authors (Shigesada et al, 1986;Maciel and Lutscher, 2013) as well as with our persistence conditions that show a population will always persist if l 2 is below a threshold value, regardless of the value of ν 2 (plot not shown). The biological explanation of this phenomenon is that an increased value of ν 2 corresponds to a larger probability of individuals to enter bad habitat and therefore decrease the chance of the population to persist.…”
Section: Analysis Of Dispersion Relationsupporting
confidence: 90%
“…The discussion in Maciel and Lutscher (2013) gives several ecological examples that make it clear that there is no single solution for all cases. For example, Thomas (2000) found that high-mobility butterflies had the highest probability of surviving in fragmented landscapes.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This aspect of movement was not considered by Shigesada et al [23], but only recently addressed by Maciel and Lutscher [16]. Based on previous work by Ovaskainen and Cornell [19], we included individual movement behaviour at an interface between two patch types into reaction-diffusion models in heterogeneous landscapes.…”
Section: Introductionmentioning
confidence: 99%